PENALARAN MATEMATIS DALAM MENYELESAIKAN SOAL PISA PADA SISWA USIA 15 TAHUN DI SMA NEGERI 1 JEMBER - Azizah, Rialita Fitri; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research is a descriptive research aimed to describe the mathematical reasoning in solving about PISA test on 15 Years Old Students in SMA Negeri 1 Jember who have high, middle, and low. Sampling was done by method Throwing Snowball until all the data can be considered saturated. The collection of data obtained from the analysis of mathematical reasoning tests, and interviews. From the results of data analysis, high ability students of mathematics tend to write what they know and asked complete without the use of symbols, write and implement a strategy properly, can write the correct final results and accompanied by the unit, reflection on the calculation and use of the formula as much as one. The middle ability students of mathematics tend to write down what they know and asked complete without the use of symbols, write and implement a strategy properly , can write the correct final result and accompanied by the unit, reflection on the part of the calculation only. While the students are capable of mathematics is low, tend to write what they know and asked complete without the use of symbols, could write one strategy execution but the steps are completion incomplete or contained wrong section and can carry out a correct strategy, can write the correct final results and accompanied by the unit, and a reflection on the calculation and use of the formula as much as one. Keywords: Mathematical Reasoning, PISA Test